Metal Deposition on a Self‐Generated Microfibril Network to Fabricate Stretchable Tactile Sensors Providing Analog Position Information. Issue 32 (26th June 2018) - Moon, Sungmin; Park, Hyung Keun; Song, Jun Hyuk; Cho, Sunghwan; Kim, Jong Chan; Kim, Junghoon; Hwang, Heesun; Kim, Hyoung Seop; Jeong, Unyong
Abstract: Stretchable conductors and sensors have attracted great attention for use in electronic skin and healthcare monitoring. Despite the development of many stretchable conductors, there are still very few studies that utilize the conventional methods making electrodes and circuits used in current industry. A method is proposed to fabricate a stretchable electrode pattern and a stretchable tactile sensor by simply depositing linear metal lines through a mask on a stretchable substrate. A method is developed of a self‐generating microfibril network on the surface of stretchable block copolymer substrates. The formation mechanism of the microfibril network is studied with finite element method simulations. Metals (Au and Ag nanowires) are deposited directly on the substrate through a patterned mask. This study shows that strain‐insensitive circuit and strain‐sensitive sensor can be fabricated in a controlled way by adjusting the thickness of the deposited metal, which makes it easy to fabricate a tactile sensor by metal deposition. Also, by using the characteristic that the sensor has different sensitivity depending on the line pattern width, a novel sensor structure simultaneously providing analog‐type position information and pressure value is proposed. Abstract : A novel strategy to fabricate stretchable tactile sensors and electrodes is presented. Metals are directly deposited through a mask on the self‐generating microfibril network surface of block copolymer elastomers. This study suggests stretchable tactile sensors that can provide analog position information and the pressure value.